Effect of dietary phosphorus and restricted feeding on performance, egg quality and serum biochemical traits of laying hens at the second production phase (Bangladesh Journal of Agriculture, 2023)
The effect of available phosphorus and restriction of feeding on the performance, egg quality, serum biochemical and yolk fatty acid profiles in laying hens at 40 to 60 weeks of age was studied. A total 540 laying hens (Lohmann Brown) aged at 40 weeks were randomly placed in a 2×3 factorial arrangement of dietary treatments including two levels of available phosphorus (AP, 0.32 and 0.45%) and three restricted feeding levels (RFL, 90, 95 and 100%) having 5 replicates in each treatment, and the experiment were conducted for twenty weeks. The results showed that dietary interaction between AP and RFL had significant effects on egg production percentage (P